Draft Annual Plan 1983-84 Volume VII Hill Areas Government of Assam - Planning Commission (Planning Commission, 1983)
The level of production achieved during the year for the Hill Areas is stated below. This year the expenditure was Rs.45.57 lakh out of total outlay of Rs.75 lakh.
Office of the Development Commissioner for the Hill Areas of Assam